2021
DOI: 10.1155/2021/9808922
|View full text |Cite
|
Sign up to set email alerts
|

Micromobility Station Placement Optimization for a Rural Setting

Abstract: Micromobility is an evolving form of transportation modality that uses small human- or electric-powered vehicles to move people short distances. Planners expected that bike sharing, the first form of micromobility, would reduce traffic congestion, cut travel cost, reduce pollution, enable connectivity with other modes of transport, and promote public health. However, micromobility options also brought new challenges such as the difficulty of placement decisions to encourage adoption and to minimize conflict wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In terms of infrastructure planning, Murray and Feng [109] was the only study that considered the mode of transport of walking and the authors were looking to determine an optimal street lighting scheme. For bike-sharing systems, problems related to infrastructure considered the location of stations [78,148,156,174]. Focusing on specific aspects of the studies, Hu et al [174] defined as decision variables the location of new stations, the removal of old ones without affecting the performance of the system, and the reallocation of docks between stations; Yang et al [78] considered dynamic demand in their problem; Askarzadeh and Bridgelall [156] considered covered activity points, such as the presence of transit stops, parks, restaurants, commercial areas, industrial centres, and universities in areas of high population density to determine the station areas; and Qian et al [148] included disadvantaged communities and park areas in their formulation.…”
Section: A Planning and Policy-makingmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of infrastructure planning, Murray and Feng [109] was the only study that considered the mode of transport of walking and the authors were looking to determine an optimal street lighting scheme. For bike-sharing systems, problems related to infrastructure considered the location of stations [78,148,156,174]. Focusing on specific aspects of the studies, Hu et al [174] defined as decision variables the location of new stations, the removal of old ones without affecting the performance of the system, and the reallocation of docks between stations; Yang et al [78] considered dynamic demand in their problem; Askarzadeh and Bridgelall [156] considered covered activity points, such as the presence of transit stops, parks, restaurants, commercial areas, industrial centres, and universities in areas of high population density to determine the station areas; and Qian et al [148] included disadvantaged communities and park areas in their formulation.…”
Section: A Planning and Policy-makingmentioning
confidence: 99%
“…For bike-sharing systems, problems related to infrastructure considered the location of stations [78,148,156,174]. Focusing on specific aspects of the studies, Hu et al [174] defined as decision variables the location of new stations, the removal of old ones without affecting the performance of the system, and the reallocation of docks between stations; Yang et al [78] considered dynamic demand in their problem; Askarzadeh and Bridgelall [156] considered covered activity points, such as the presence of transit stops, parks, restaurants, commercial areas, industrial centres, and universities in areas of high population density to determine the station areas; and Qian et al [148] included disadvantaged communities and park areas in their formulation. Related to rail systems, Kang et al [152] aimed at selecting the points of intersections of the new railway alignment, while Chen et al [154] sought to determine the locations and capacity of railbased park-and-ride sites.…”
Section: A Planning and Policy-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Loidl et al (2019) identified preferred locations for bike stations using a spatial framework and overlay analysis with demographic characteristics [28]. Askarzadeh and Bridgelall (2021) solved a location-allocation problem using a spatial optimization model within a geographic information system (GIS) framework and identified the best locations for five new bikesharing stations in Fargo, North Dakota [29].…”
Section: Vertiport Locatingmentioning
confidence: 99%
“…Yet, station-based versions of these services can still increase access to essential opportunities in lower-density urban areas. To this end, station location needs to be optimised by considering local characteristics, such as the location of places of interest like shopping centres or education institutions (Askarzadeh & Bridgelall, 2021). Car and other long-ranged vehiclesharing services can be particularly suited to respond to the needs of less dense areas, especially those with potentially higher car dependency.…”
Section: Electric Vehicles For Shared Passenger Vehicle Servicesmentioning
confidence: 99%